2017
DOI: 10.3389/fmicb.2017.00437
|View full text |Cite
|
Sign up to set email alerts
|

Host Factors in the Infection Cycle of Bamboo mosaic virus

Abstract: To complete the infection cycle efficiently, the virus must hijack the host systems in order to benefit for all the steps and has to face all the defense mechanisms from the host. This review involves a discussion of how these positive and negative factors regulate the viral RNA accumulation identified for the Bamboo mosaic virus (BaMV), a single-stranded RNA virus. The genome of BaMV is approximately 6.4 kb in length, encoding five functional polypeptides. To reveal the host factors involved in the infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…The study of differentially expressed genes after virus infection is a strategy for identifying host factors involved in virus infection cycles. We used a cDNA-AFLP technique to identify a number of these genes (Cheng et al ., 2010) and revealed their involvement in BaMV infection (Huang et al ., 2017a). One of the host factors in this study was demonstrated to play a defensive role against BaMV replication.…”
Section: Discussionmentioning
confidence: 99%
“…The study of differentially expressed genes after virus infection is a strategy for identifying host factors involved in virus infection cycles. We used a cDNA-AFLP technique to identify a number of these genes (Cheng et al ., 2010) and revealed their involvement in BaMV infection (Huang et al ., 2017a). One of the host factors in this study was demonstrated to play a defensive role against BaMV replication.…”
Section: Discussionmentioning
confidence: 99%
“…As a native pathway of NbEILP for sensing the elicitors from pathogens, NbEILP is synthesized and retained on the ER membrane and is possibly secreted to the plasma membrane as vesicle trafficking. The movement complex containing TGBp1, vRNA, replicase, CP, TGBp2, and TGBp3 of BaMV ( Chou et al, 2013 ; Huang et al, 2017 ) might take advantage of the secretory path of NbEILP to reach the plasmodesmata for cell-to-cell movement. Therefore, the possible role of NbEILP in BaMV movement could be gathering these viral- or host-encoded movement-associated proteins together.…”
Section: Discussionmentioning
confidence: 99%
“…The coding capacity of a small viral RNA genome is limited to facilitate the infection and replication cycle; the RNA virus requires different host proteins directly or indirectly to assist its accumulation ( Ahlquist et al, 2003 ; Hyodo and Okuno, 2016 ; Nagy, 2016 ). A few host proteins associated with viral RNA or the RdRp complex are involved in BaMV replication such as the chloroplast phosphoglycerate kinase, heat-shock protein 90, and glutathione S -transferase U4 ( Huang et al, 2017 ). The host proteins RabGTPase-activating protein 1, serine/threonine kinase-like protein, and casein kinase 2α participate in BaMV movement ( Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo mosaic virus (BaMV) is a well-studied species in the genus Potexvirus, family Alphaflexiviridae Cheng, 2017;Huang et al, 2017). Its positive-strand RNA genome is 6366 nt (excluding the 3 0 poly(A) tail) and contains five open reading frames (Lin et al, 1994;Yang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%